Heart Transplantation in a Toddler with Cardiac Kawasaki Disease - Tirilomis, Theodor; Steinmetz, Michael; Grossmann, Marius; Bräuer, Anselm; Paul, Thomas; Ruschewski, Wolfgang; Schöndube, Friedrich A. (Frontiers in Surgery, 2017)
Kawasaki disease is very rare in Western Europe. The disease may involve coronary arteries. A 2-year-old boy with the diagnosis of Kawasaki disease had had seizure-like symptoms. Further evaluation revealed recurrent myocardial ischemia and myocardial infarction. Due to extraordinary extension of the coronary disease myocardial revascularization was not feasible and the toddler underwent successful heart transplantation after 97 days on waiting list.